The Effect of Theobromine Supplementation on HDL‐c Subclasses (HDL‐c2, HDL‐c3), HDL‐c2/HDL‐c3 Ratio, and Gene Expression of PPAR‐α and Sirt1 in Subjects With Metabolic Syndrome: A Randomized Controlled Clinical Trial - Sharifi‐Zahabi, Elham; Dastafkan, Zahra; Asadi, Amirhossein; Hosseini‐Baharanchi, Fatemeh Sadat; Rezvani, Nayebali; Yari, Saba; Shidfar, Farzad (Food science & nutrition, 2025)
ABSTRACT Several studies have reported the beneficial effects of theobromine (TB) on metabolic syndrome (MetS) indices and cardiovascular risk factors. However, the findings are controversial. The current study aimed to examine the effects of a 12‐week intake of pure TB in combination with a low‐calorie diet on serum levels of HDL‐c2, HDL‐c3, the HDL‐c2/HDL‐c3 ratio, and the gene expression of peroxisome proliferator‐activated receptor alpha (PPAR‐α) and silent information regulator 1 (Sirt1) in overweight and obese adults with MetS. In this randomized clinical trial, 80 participants with MetS were randomly allocated to intake a 450 mg/day TB or placebo in combination with a low‐calorie diet for 12 weeks. Dietary intake, anthropometric indices, fasting serum levels of HDL‐c2 and HDL‐c3, the HDL‐c2/HDL‐c3 ratio, and the gene expression of PPAR‐α and Sirt1 were assessed at the start and end of the study. The sample size at completion was n = 72 subjects. Our findings revealed that TB supplementation significantly increased HDL‐c (0.34 ± 2.11 vs. −1.24 ± 3.09; p = 0.041), HDL‐c2 (0.95 ± 1.8 vs. −0.26 ± 1.30; p < 0.001), the HDL‐c2/HDL‐c3 ratio (0.04 ± 0.45 vs. 0.01 ± 0.04; p = 0.004), and the gene expression of PPAR‐α (0.884 ± 0.195 vs. 0.332 ± 0.178; p = 0.004) compared to the placebo. The results of the current study showed that TB supplementation led to an increase in serum levels of HDL‐c2, the HDL‐c2/HDL‐c3 ratio, and the gene expression of PPAR‐α in subjects with MetS. Trial Registration: IRCT20091114002709N59 The results of the current study showed that theobromine supplementation led to an increase in serum levels of HDL‐c2, HDL‐c2/HDL‐c3, and gene expression of PPAR‐α in subjects with MetS.